Media–state relations in Burundi: Overview of a post-traumatic media ecology. Issue 2 (2nd April 2016) - Kane, Oumar; Bizimana, Aimé-Jules
ABSTRACT: Through an analysis of the relations between the state and the media in Burundi, this article aims to problematise these actors' interactions within a context characterised by an asymmetry of power in favour of political authorities and some leeway enjoyed by the media. Through a review of a corpus constituted of scientific literature, reports documenting the situation of press freedom in the country, and newspaper articles, the present article shows that the legal framework governing media activity is rather protective of press freedom, despite some recent setbacks. Under this protective media context, the state uses a variety of devious means to strengthen its grip on the media sector and on journalists. The media, for their part, are obliged to manoeuvre in a post-traumatic context where issues of security have a strong public legitimacy. The article shows that in order to understand relations between the Burundian state and the media, it is necessary to place them in an asymmetrical power context where both face constraints and enjoy spaces of tactical intervention.